Strategic Planning in a Student-Run Clinic: Utilizing a Tiered Meeting Model to Evaluate Clinical Needs - Francesca Andronic; Zachary Goldstein; Rachel Lockard; Brian Park; Christopher Terndrup (Journal of Student-Run Clinics, 2021)
The Bridges Collaborative Care Clinic (BCCC) is Oregon’s first and only interdisciplinary, student-run clinic that provides free health and social services to underserved populations. The hierarchical leadership structure utilized by the clinic since its inception in 2016 worked effectively in the early stages of development. As the clinic matured, increasing complexity of programs and administrative duties led to lapses in communication and loss of information between teams, resulting in decreased efficiency and impact as measured by clinical output. Student volunteers and the BCCC Board of Directors recognized the need for organizational change and proposed developing a strategic plan. This paper describes the process, outcomes, and limitations faced by BCCC throughout its strategic planning. The Quality Function Deployment (QFD) model was implemented because of its collaborative approach of involving the customers—people who receive the services—in order to shape future initiatives for the organization. In this case, the QFD defines the customers as the participants who are seeking care at the clinic. The outcomes of the strategic planning process are expected to help the clinic function more efficiently and include a prioritized list of participant-defined needs, a list of solutions, and a timeline to guide new projects. By illustrating the implementation of QFD and its potential complications, other student-run clinics that are seeking improvement can replicate or adapt this method to develop their own strategic planning processes.